A Systematic Review of in-vivo Studies on Dietary Mushroom Supplementation for Cognitive Impairment (P14-021-19) - Nkodo, Amelie (Curr Dev Nutr, 2019)
OBJECTIVES: A systematic review was undertaken of the evidence on the use of Hericium erinaceus (Reishi), Ganoderma lucidum (Lion's Mane), Ophiocordyceps sinensis (Cordyceps) and Cordyceps militaris (Cordyceps), dietary supplementation on cognitive impairment outcomes. METHODS: Relevant articles were identified in major databases (PubMed, Embase, Web of Science, and SCOPUS). Key search words were Hericium erinaceus, Ganoderma lucidum, Ophiocordyceps sinensis, Lion's mane, Reishi, Cordyceps, cognitive, memory, dementia, Alzheimer's. Included studies were peer-reviewed in-vivo articles published in English before January 2019, with cognitive outcomes. RESULTS: Twenty-five (25) of 194 studies met the inclusion criteria: eight (8) studies on lion's mane mushroom, seven (7) studies on reishi mushroom and ten (10) studies on cordyceps mushroom. Three (3) randomized-controlled trials were included in this review. Studies varied by animals used, preparation of supplement, dosage and duration of supplementation, and cognitive outcomes. Twenty-two (22) animal studies found positive results (P < 0.05) on at least one of the doses tested for at least one cognitive impairment outcome. Of the human trials, two (2) studies found positive results (P < 0.05) on at least one of the cognitive assessments. CONCLUSIONS: Despite heterogeneous study design, the results of this review suggest that dietary supplementation with lion's mane, reishi and cordyceps mushrooms may have a beneficial effect on cognitive impairment. Further clinical research studies are needed to demonstrate the potential medicinal benefits of dietary mushroom supplementation in humans with cognitive impairments. FUNDING SOURCES: No external funding.